MANAJEMEN PENGEMBANGAN MUTU LEMBAGA PENDIDIKAN (Studi di Madrasah Ibtidaiyah Negeri (MIN) Tempel Yogyakarta) - Alfian Eko Rochmawan (MAMBA'UL 'ULUM, 2019)
Islamic Elementary education institutions Negri Tempel is an institution engaged in education on the basis of Islamic education that is inseparable from the competition and competition from other Islamic educational institutions. Tempel State Islamic Elementary School is an institute under the auspices of the Ministry of Religion. The purpose of its establishment is to increase the intelligence, knowledge, personality, character, and skills to live independently and to follow further education, which is expected to be achieved and sustained total liability. This study aims to present how the development of quality management in the State Government Elementary School Tempel covering Planing, Organizing, Actuating, Controlling. Inside analysis by looking kekutan institutions namely the implementation and development of quality educational institutions. The result is that the State Government Elementary School Tempel Yogyakarta has different characteristics with other agencies like Islamic Elementary. The development of quality educational institutions can be reviewed through the theory of planning, organizing, supervision or control. In plain practical management functions have been implemented in the State Islamic Elementary Tempel Yogyakarta and has been implemented effectively. Thus the implementation of the development of quality management education institutions in general have a direct impact on the management of the State Government Elementary School in Yogyakarta Tempel. Cooperation institutions have been embedded in every teachers, employees and students so as to produce graduates who are high achievers, moral qur'ani, confident, healthy and innovative environmentally sound.